FORMATION OF CULTURAL POLICY OF PUBLIC MANAGEMENT OF MUSIC EDUCATION - SHESTAKOVSKA, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the features of the formation of cultural policy of public management of music education in Ukraine and the world. The main mechanisms of state regulation in this area are analyzed, in particular, financial support, decentralization of management, international cooperation and integration of music education into the general system of cultural policy. The main challenges facing music education in Ukraine are identified, including insufficient budget funding, outdated material and technical base, as well as an insufficient level of international integration. Special attention is paid to foreign experience, in particular, to European models of support for music education, which are based on public-private partnerships, grant programs and regional cultural hubs. The role of the state in the formation of effective cultural policy and the possibility of adapting the best world practices to Ukrainian conditions are investigated. In particular, examples from Germany, France, Great Britain and the USA are considered, where music education receives support at both the state and local levels, and cooperation with civil society and the private sector allows ensuring financial stability and quality of educational programs. Particular attention is paid to the issue of the development of music education in Ukraine in conditions of military conflict, when culture plays an important role in preserving national identity and psychological support of society. Strategic directions for reforming the music education system are identified, in particular the need to expand financial support mechanisms, update the material and technical base of educational institutions, as well as intensify international cooperation. The purpose of the article is to analyze the mechanisms for forming the cultural policy of public management of music education, study the European experience and develop recommendations for its adaptation to Ukrainian conditions. The main objectives of the research are to determine the principles of effective management of the cultural sphere, analyze foreign practices in the field of music education, identify key problems of the domestic system of art education and develop proposals for its reform. The results obtained can be used to develop strategic documents in the field of cultural policy aimed at ensuring the sustainable development of music education in Ukraine.